2001
DOI: 10.1136/adc.84.4.324
|View full text |Cite
|
Sign up to set email alerts
|

An audit of RCP guidelines on DMSA scanning after urinary tract infection

Abstract: Aim-To assess the outcome of imaging investigations carried out in children with urinary tract infection (UTI), to compare the investigations with national guidelines, and to assess the impact on management. Methods-Retrospective review of inpatients and outpatients, aged 0-12 years, referred to the University Hospital of Wales Healthcare Trust between February 1997 and January 1998 with UTI. All children without bacterial evidence of UTI and children previously investigated for antenatal urological anomalies,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…As age increased the proportion decreased to 29% in 3-5 years of age and to 15% over 5 years. The results were similar to the study conducted by Deshpande PV et al 13 In his study 34% children under 1 year presented with VUR and 20% of children were found to have VUR on VCUG in between 1-6 years of age. On analyzing the sex distribution of children with VUR, we found that among first UTI there is not much difference in distribution of VUR among males and females.…”
Section: Discussionsupporting
confidence: 89%
“…As age increased the proportion decreased to 29% in 3-5 years of age and to 15% over 5 years. The results were similar to the study conducted by Deshpande PV et al 13 In his study 34% children under 1 year presented with VUR and 20% of children were found to have VUR on VCUG in between 1-6 years of age. On analyzing the sex distribution of children with VUR, we found that among first UTI there is not much difference in distribution of VUR among males and females.…”
Section: Discussionsupporting
confidence: 89%
“…6,7 Also, most of the pediatric nephrologists prefer to rely on clinical and biological findings in case of complicated UTI rather than scintigraphy. 8,9 However, it sometimes happens that clinical findings and equivocal urine cultures do not favor diagnosis, even though the patient may already have UTI and renal damage. 10,11 This prospective clinical study was carried out to indicate any correlation between the incidence of renal scarring following acute pyelonephritis and previously well-known risk factors such as vesicoureteral reflux (VUR), age and recurrent urinary tract infections.…”
Section: Original Articlementioning
confidence: 99%
“…Only 16 (20%) children had neurogenic bladder. The median duration of fever was 3 days (range [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Other paraclinical findings were as follows: CRP level of more than 6 mg/dL was reported in 61 (76.2%) children; leukocytosis in 42 (52.5%); and positive culture for Escherichia coli was obtained from 69 (86.2%) and the rest of the patients had other urinary microbial profiles.…”
Section: Clinical and Paraclinical Findingsmentioning
confidence: 99%
“…E ditor ,—Deshpande and Verrier Jones have recently concluded that it is not worth undertaking dimercaptosuccinic acid (DMSA) scans in children over 1 year of age who present with a “simple” urinary tract infection (UTI) 1. Their argument has three strands.…”
mentioning
confidence: 99%